1991
DOI: 10.1111/j.1432-1033.1991.tb21073.x
|View full text |Cite
|
Sign up to set email alerts
|

The devapamil‐binding site of the purified skeletal muscle receptor for organic‐calcium channel blockers is modulated by micromolar and millimolar concentrations of Ca2+

Abstract: The interaction of 2,7-dimethyl-3-(3,4-dimethoxyphenyl)-3-cyan-7-aza-9-(3-methoxyphenyl) nonahydrochloride (devapamil), a stereospecific analog of {3-[2-(3,4-dimethoxyphenyl)ethyl]-methylaminopropyl-3,4-dimethoxy-(1 -methylethyl)benzeneacetonitrile (verapamil), with the purified skeletal muscle receptor for calcium channel blockers (CaCB) was studied at 4OC and 30 "C in the absence and presence of calcium. The purified CaCB receptor bound 0.9 mol devapamil/mol calcium-channel c (~ subunit, with an apparent Kd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
3
9
0
Order By: Relevance
“…As shown previously, the association reaction followed second-order kinetics, the initial association rate increasing linearly with the concentration of ligand (Brauns et al, 1995). As discussed in the Materials and Methods section, the association reaction was accompanied by an irreversible inactivation of binding activity due to slow denaturation of the channel in detergent solution (Schneider et al, 1991).…”
Section: Dhps Slow the Binding Kinetics Of Dmbodipy-bazsupporting
confidence: 63%
“…As shown previously, the association reaction followed second-order kinetics, the initial association rate increasing linearly with the concentration of ligand (Brauns et al, 1995). As discussed in the Materials and Methods section, the association reaction was accompanied by an irreversible inactivation of binding activity due to slow denaturation of the channel in detergent solution (Schneider et al, 1991).…”
Section: Dhps Slow the Binding Kinetics Of Dmbodipy-bazsupporting
confidence: 63%
“…The regulatory effects of (Ϫ)-D600 and diltiazem are thought to be coupled to or mediated by Ca 2ϩ binding sites in L-type Ca 2ϩ channels (32,33). In previous studies, we demonstrated that the effect of (Ϫ)-D600 differed in skeletal muscle and in cells expressing the skeletal muscle ␣ 1 subunit (34).…”
Section: Effects Of Subunits On Allosteric Regulation Of Dihydropyridmentioning
confidence: 87%
“…This agent blocks the same cardiac Ca2+-currents as the dihydropyridine antagonists (Lee and Tsien, 1983) and an w-conotoxininsensitive current in motor nerves (Anderson and Harvey, 1987). Using the rate constant data for the binding of verapamil to purified channel protein (Schneider et al, 1991), assuming a mean duration of the action potential of 1 ms and pseudo-first order kinetics with no dissociation between impulses, then it would appear that in angel's experiments -95% of channels should have been bound with the antagonist at the end of a 200 impulse train if they were opened.…”
Section: Discussionmentioning
confidence: 99%